STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES - Endang Kusniati (Universitas Islam Negeri Fatmawati Sukarno, 2016)
This paper discusses strategies based learning multiple intelligences. Which has focused on the concept of multiple intelligences based learning strategies, training and developing 8 (eight) value of intelligence (Multiple Intelligences) and the contribution of multiple intelligences learning strategy based on National Education. Theory of multiple intelligences triggered by Howard Gardner, is used as an analytical tool, ie linguistic, logical-mathematical, spatial, musical, kinesthetic, interpersonal, and intrapersonalnya, natural. To know the trend of the intelligence of every child in the concept of multiple intelligences will be tested using the research of Multiple Intelligences Research (MIR). With MIR teachers will be easier knowing the tendency of students’ intelligence. While the contribution of MI in the national education is to terbinanya based schools multiple intelligences, such as SDIT-SMPIT Al-Bina Pangkalpinang, SMP YIMI Gresik, and 95 other schools